Resealed Erythrocytes: As a Carrier for Drug Targeting - Rewar, Suresh; Bansal, B K; Rathore, P S; Singh, C J; Gupta, L (Asian Journal of Pharmaceutical Research and Development, 2014)
Now a day’s most of the investigations are focused only on the development of various drug delivery systems for targeting of the desired tissue to achieving required therapeutic concentration with less amount of dose. Erythrocytes are biocompatible, biodegradable, possess long circulation half lives, and can be loaded with a variety of biologically active compounds using various chemical and physical methods. Erythrocytes have been the most interesting carrier and have found to possess great potential in drug targeting. Resealed erythrocytes are gaining more popularity because of their ability to circulate throughout the body, biocompatibility, zero order release kinetics, reproducibility and ease of preparation. Most of the resealed erythrocytes used as drug carriers are rapidly taken up from blood by macrophages of reticuloendothelial system (RES), which is present in liver, lung, and spleen of the body. The aim of the present review is to focus on the various features, drug loading technology and biomedical application of resealed erythrocytes.